Wisdom and love in Saint Thomas Aquinas / Under the auspices of the Aristotelian Society of Marquette University. - Gilson, Etienne, 1884-1978. (Aquinas lecture, 1951)
The Aristotelian Society of Marquette University each year invites a scholar to speak on the Philosophy of St. Thomas Aquinas. Those lectures have come to be called the Aquinas Lectures and are customarily delivered on the Sunday nearest March 7, the feast day of the Society's patron saint.